2008
DOI: 10.1080/08037050802059225
|View full text |Cite
|
Sign up to set email alerts
|

Arterial stiffness indices in healthy volunteers using non‐invasive digital photoplethysmography

Abstract: Digital photoplethysmography is a portable, operator-independent, reproducible and simple method of measuring arterial stiffness. Ranges of normality of arterial stiffness will depend on the individual's age, race, lipid levels, HR and blood pressure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
39
0
3

Year Published

2013
2013
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 29 publications
7
39
0
3
Order By: Relevance
“…As our second objective was correlation between RI and SI, which is found to be significant. Study performed by Brilliante et al, showed a significant correlation of RI and SI with age, heart rate, systolic blood pressure and diastolic blood pressure [21].…”
Section: Resultsmentioning
confidence: 91%
“…As our second objective was correlation between RI and SI, which is found to be significant. Study performed by Brilliante et al, showed a significant correlation of RI and SI with age, heart rate, systolic blood pressure and diastolic blood pressure [21].…”
Section: Resultsmentioning
confidence: 91%
“…The present study agrees with findings on BP in another study. 41 RI at rest reflects the current state of arterial tone, 16,17 and a lower RI is an indicator of more relaxed arteries. Also FST reflects blood flow 42, 43 and is regulated by sympathetic tone, 44 which relates FST to RI and endothelial function, 45 but not to SI.…”
Section: Discussionmentioning
confidence: 99%
“…Among the young population, lack of health screening may also predispose to increase CVD prevalence finger arterial bed and is influenced by several factors such as ventricular ejection, aortic and peripheral arterial stiffness (AS), peripheral arterial resistance and blood viscosity (Elgendi 2012;Millasseau et al 2002). Several common parameters that were derived from finger PPG are stiffness index (SI), reflection index (RI), crest time and a, b, c, d and e waves, and all were proposed to be indices of vascular function and vascular ageing (Millasseau et al 2002;Brillante et al 2008;Baek et al 2007;Hashimoto et al 2005;Takazawa et al 1998;Tsai et al 2007).…”
Section: Introductionmentioning
confidence: 99%